DG planning with amalgamation of economic and reliability considerations. (December 2015) - Battu, Neelakanteshwar Rao; Abhyankar, A.R.; Senroy, Nilanjan
Highlights: Optimal location for DG is found by coupling reliability and economic aspects. A combined performance index for reliability ( ENS ) and total cost ( TC ) is developed. Combined index helps in resolving trade-off between cost and reliability objectives. A new approach is developed to evaluate the optimal load that can be dispatched by DG. The proposed approach is applied to a 15-bus and 18-bus radial distribution system. Abstract: Distributed generation has been playing a vital role in dealing with issues related to distribution systems. This paper presents an approach which provides the distribution system operator with a set of solutions for DG placement to optimize reliability and total cost of power consumed by the distribution system. Optimal location of a Distributed Generator is evaluated based on the performance indices derived for reliability index and total cost of power consumed by the system. The proposed approach is applied to a 15-bus radial distribution system and a 18-bus radial distribution system and the results are analyzed.